On the Interpretation of Hysteresis Loop for Electronic and Ionic Currents in Organic Memristive Devices. Issue 18 (21st September 2020) - Battistoni, Silvia; Verna, Alessio; Marasso, Simone Luigi; Cocuzza, Matteo; Erokhin, Victor
Abstract : Organic Memristive Devices Organic memristive devices are crucial elements for the mimicking important synapse properties, such as memory and learning. For their larger uses in neuromorphic computation, it is necessary to improve their rate of the resistance switching and their stability. In article number 1900985, Silvia Battistoni, Victor Erokhin, and co‐workers report a new approach, based on the use of a liquid electrolyte, for obtaining higher stability and faster resistive switching.